Simeon of Polotsk: the „Financial Portrait” - Лаврентьев, Александр; Преображенская, Aнастасия (Slavia Orientalis, 2020)
The study looks into the wealth and earnings of the first Russian court poet of the 17th century, Simeon of Polotsk (1629‑1680). Simeon was in many respects a unique figure for 17th‑century Muscovy. His social status was far from common for besides being a regular hieromonk, at the same time he founded and managed a printing house supported by Tsar Aleksey Mikhajlovich (an institution that printed books without the license of the Moscow patriarch), and was probably the only monk to be accepted to the Tsar’s service as a poet and preacher. His private life and especially fortune are fascinating: residing in a house specially built for him on the territory of the Zaikonospasskiy monastery in Moscow, Simeon earned his living rather than live by the means provided by his monastery and by the end of life he had accumulated a great sum of Russian silver kopeks and golden chervonets comparable in worth to the money princes would have had for charitable donations at their funerals. When living in Moscow, Simeon received everything needed for his everyday life from the Tsar’s court: food, hay for his horse (provided by the Tsar as well), paper for writing. The supplement to the article discusses the date of Simeon’s relocation to Moscow from Polotsk and examines the circumstances under which he was accepted to the royal court.
Keywords: Simeon of Polotsk; poet; last will; roubles; chervonets